Histone deacetylase AtSRT2 regulates salt tolerance during seed germination via repression of vesicle-associated membrane protein 714 (VAMP714) in Arabidopsis - Tang, Wen-Si (The New phytologist, 2022)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.